KETEBALAN OPTIMAL KACA PADA PENGAPLIKASIAN AKUARIUM DAN GLASSPOND - Jimmy Leonardy Lim; Wati Asriningsih Pranoto (JMTS: Jurnal Mitra Teknik Sipil, 2022)
Indonesia is a country rich in fauna species, especially ornamental fish. There are about 8500 species of fish and 1300 of them are fish that live in fresh water. This fish diversity is one of the factors that triggers the growth of the economic sector in the hobby sector in the form of maintaining ornamental fish. The maintenance of this ornamental fish requires a container so that it can be enjoyed directly. Commonly used containers are aquariums and glassponds. In the process of making this aquarium and glasspond requires glass material. Glass itself has a special property that is transparent but easily broken. The load on the total volume of water accommodated by the aquarium and glasspond is a major factor in the selection of the thickness and type of glass. This research focuses on 8 mm and 12 mm glass thickness for aquarium and 12 mm tempered type for glasspond. By calculating and analyzing the total water load and the strength of the glass in holding the water load, the optimal glass thickness is obtained in water structures such as aquariums and glassponds.